Solvent- and catalyst-free N-formylations of amines at ambient condition: Exploring the usability of aromatic formates as N-formylating agents. Issue 2 (17th January 2017) - Batuta, Shaikh; Begum, Naznin Ara
ABSTRACT: A solvent- and catalyst-free N- formylation protocol has been developed for amines (1s–21s ) where aromatic formates (1r–6r ) were used as the N- formylating agents. The amine substrates include both primary and secondary aromatic amines (1s–19s ) as well as aliphatic amine (20s ) and a primary amide (21s ). Structures of both the aromatic formate and amine components strongly influenced the rate of the reaction and yield of the N- formamide products. The reaction condition is mild and easy to operate. This protocol can be done smoothly under ambient conditions and gives high yield of formamide products. Furthermore, the present method cannot be applied for the formylation of thiol group (22s ). This signifies its possible use for the chemoselective N- formylation of amine in the presence of thiol functionality. GRAPHICAL ABSTRACT: